Lipocalin 2 expression promotes tumor progression and therapy resistance by inhibiting ferroptosis in colorectal cancer. Issue 7 (5th July 2021) - Chaudhary, Nazia; Choudhary, Bhagya Shree; Shah, Sanket Girish; Khapare, Nileema; Dwivedi, Nehanjali; Gaikwad, Anagha; Joshi, Neha; Raichanna, Jinsy; Basu, Srikanta; Gurjar, Murari; P.K., Smitha; Saklani, Avanish; et al.
Abstract: Lipocalin 2 is a siderophore‐binding protein that regulates iron homeostasis. Lipocalin 2 expression is elevated in multiple tumor types; however, the mechanisms that drive tumor progression upon Lipocalin 2 expression remain unclear. When Lipocalin 2 is over‐expressed, it leads to resistance to 5‐fluorouracil in colon cancer cell lines in vitro and in vivo by inhibiting ferroptosis. Lipocalin 2 inhibits ferroptosis by decreasing intracellular iron levels and stimulating the expression of glutathione peroxidase4 and a component of the cysteine glutamate antiporter, xCT. The increase in xCT levels is dependent on increased levels of ETS1 in Lipocalin 2 over‐expressing cells. Inhibiting Lipocalin 2 function with a monoclonal antibody leads to a decrease in chemo‐resistance and transformation in vitro, and a decrease in tumor progression and chemo‐resistance in xenograft mouse models. Lipocalin 2 and xCT levels exhibit a positive correlation in human tumor samples suggesting that the pathway we have identified in cell lines is operative in human tumor samples. These results indicate that Lipocalin 2 is a potential therapeutic target and that the monoclonal antibody described in our study can serve as the basis for a potential therapeutic in patients who do not respond to chemotherapy.